ENT 530 Social Media Portfolio: Heeladina / Nurul Adlina Mohammad Norhan - Mohammad Norhan, Nurul Adlina (2021)
Heeladina is a brand that sell various types of women scarf for example shawl, square scarf (bawal), and inner snow cap. Heeladina also come out with unisex oversized knitwear that is suitable to be wear by women and also men. All products from Heeladina are very high in quality and we are focusing to give the best products in term of material to increase our customers’ satisfaction. Our business is based in Malaysia and we have only one outlet that become our packing area that we decided to open at Ampang Jaya area in Selangor. Heeladina was started in the end of the year of 2020 and operate the business fully at home with no physical store or any physical outlet. Heeladina also operate an online shopping platform using a Facebook (FB) page which is Heeladina – By Nurul Adlina Binti Mohammad Norhan to make all the customers peacefully placed their order and making payment with a simple way. In the early of 2021, Heeladina lease a store to make it easier to operate the business in term of packaging the product that will be ship to the customers as from time to time, the business getting more customers and widely known to our customers and in Malaysia.